Prosthetic rehabilitation of a patient with a palatal fistula and an atrophic mandibular ridge using admix material to record the neutral zone: A case report - Manu Rathee; Surbhi Mittal; Maqbul Alam; Sarthak Singh Tomar; Kritika Diwan (Mashhad University of Medical Sciences, 2023)
Objective: In this case report, we employed an admix material to record the neutral zone in a patient presenting with a palatal fistula and an atrophic mandibular ridge.Case report: In this case report, we present a 67-year-old edentulous female with a history of oropharyngeal carcinoma affecting the soft palate. A circular palatal fistula, measuring approximately 8mm×8mm, was identified at the junction of the hard and soft palate. The mandibular residual ridge displayed significant atrophy. The neutral zone was recorded using admix material, comprising three parts by weight of impression compound and seven parts by weight of tracing compound. The fabricated dentures yielded favorable outcomes in terms of denture stability, and patient comfort. The patient reported the absence of nasal regurgitation and a notable improvement in speech production due to the obturator prosthesis.Conclusion: The neutral zone impression technique with admix impression material provided successful results in constructing both a mandibular complete denture and a maxillary denture with an obturator.  The retention and stability of the complete denture were desirable and the patient was satisfied with the outcome.